1989
DOI: 10.1093/infdis/159.3.549
|View full text |Cite
|
Sign up to set email alerts
|

Association of Tuberculosis and M. tuberculosis-Specific Antibody Levels with HLA

Abstract: In the search for HLA-linked immune response genes that control susceptibility to tuberculosis, we performed HLA typing and measured antibody titers to well-defined Mycobacterium tuberculosis antigenic determinants in 101 patients with sputum smear-positive pulmonary tuberculosis and 64 healthy controls from Surabaya, Indonesia. HLA-DR2 and DQw1 were associated with sputum smear-positive pulmonary tuberculosis (attributable risk = 36% and 39%, respectively), while DQw3 was associated even more strongly with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
78
2

Year Published

1992
1992
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 157 publications
(81 citation statements)
references
References 29 publications
1
78
2
Order By: Relevance
“…In the Tb patients, the reactivity frequency (60%) observed for this protein was similar to that observed by others [32]. Its strong association with HLA antigens [33], and its relation with the presence of cavitary [34] processes, explains the variation in sensitivity values reported by different investigators, which depends on the population under investigation. For the antigens in the 16 kDa range, we found 50% reactivity.…”
Section: Discussionsupporting
confidence: 84%
“…In the Tb patients, the reactivity frequency (60%) observed for this protein was similar to that observed by others [32]. Its strong association with HLA antigens [33], and its relation with the presence of cavitary [34] processes, explains the variation in sensitivity values reported by different investigators, which depends on the population under investigation. For the antigens in the 16 kDa range, we found 50% reactivity.…”
Section: Discussionsupporting
confidence: 84%
“…[125][126][127][128] However, there is evidence for heterogeneity as not all populations studied demonstrate the HLA-DR2 effect. 129 A more recent study of patients and controls from Cambodia found an association between HLA-DQB1*0503 and tuberculosis, and this needs investigation in other populations.…”
Section: Major Histocompatibility Complexmentioning
confidence: 99%
“…Human Leucocyte Antigen (HLA) genes are implicated in the spectral clinical manifestations characteristic of both tuberculosis and leprosy [119]. The limited data obtained may indicate an association of HLA-DR2 and pulmonary tuberculosis [120,121]. In mice, H-2 linked genes are known to control both granulomatous responses and resistance to M. lepramurium [122].…”
Section: Genetic Factors In Resistance To Tuberculosismentioning
confidence: 99%